ANALISIS STRATEGI PENGEMBANGAN PARIWISATA KAWASAN SELAT LEMBEH DI KOTA BITUNG - Ellen R. Sutrisno; Charles R. Ngangi; Caroline B. D. Pakasi (Sam Ratulangi University, 2018)
This study aims to analyze the strategy of tourism development of Lembeh Strait Region in Bitung City. The study was conducted in the Lembeh Strait Area of Bitung City, which covers the Lembeh Island region and the mainland of Bitung City. The study took place in March 2018. This research used kuantitatif descriptive method. The data source consists of primary data and secondary data. Primary data is obtained directly from the field through the respondents who have been determined, while secondary data obtained from agencies or institutions - related institutions such as the Tourism Office, BPS Bitung, libraries and other relevant SKPD ie Tourism Office, Bappeda, Investment and One Stop Service Office. Sample collection used technique of Accidental and Purposive Sampling. Data collection technique used in this research is Field Survey. Researchers prepare and retrieve data through surveys, questionnaires, document studies, interviews, documentation. This study uses SWOT data processing analysis through process analysis of Internal factors and External factors. The result of this research shows that the strategy of tourism development of Lembeh Strait area in Bitung City based on SWOT analysis is in the first quadrant between external opportunity and internal strength where the result of analysis obtained by total score of Internal Factor Analysis (IFAS) is 3.076 and External Factor Strategic Analysis Summary (EFAS) is 3.396. The main strategy in developing Lembeh Strait area tourism that must be implemented is to develop and improve the factors of Attraction, Accessibility and Amenities as follows: (1) Maintaining the beauty and uniqueness of nature Lembeh Strait as the main Attraction and adding new artificial attraction object; (2) Completing and improving public facilities and tourism facilities and facilities and infrastructure; (3) Make intelligent use of social media communication information technology as a cheap and efficient means of promotion.*eprm*.